Percutaneous nephrostomy experience in pediatric patients: comparison of fine and thick needle techniques - Nas, Omer Fatih; Oztepe, Muhammet; Candan, Selman; Kandemirli, Sedat Giray; Bilgin, Cem; İnecikli, Mehmet Fatih and Özkaya, Güven and Ongen, Gokhan and Erdogan, Cüneyt (The European Research Journal, 2023)
Objectives: The aim of this study is to assess the effect of needle size in pediatric percutaneous nephrostomy (PN) placement in terms of complications and success rates. Methods: Seventy one percutaneous nephrostomies were performed in 51 patients aged 1 month to 18 years (mean 6.03 ± 5.88 years) between May 2012 and March 2020. Demographic data, indication for PN placement, puncture technique (calyceal entry level: upper, middle, lower pole or pelvis) and needle size, anesthesia type (general or local anesthesia), duration of catheter use and complications were retrospectively retrieved from the hospital electronic recording system. Results: Thirty procedures were performed using a 21 gauge needle and 41 procedures using a 18 gauge needle. There was no statistically significant difference between the two groups in terms of age, gender, degree of hydronephrosis, and calyceal entry level. Technical success and complication rates were similar in two groups (p = 0.423). Conclusions: In the pediatric age group, both 18 and 21 gauge needle techniques can be used safely based on the preference of the interventionalist.